THE ROLE OF THE DISASTER PREPAREDNESS TEAM IN CENTRAL LOMBOK - Budiman, Lalu; Akbar, L M.T; RASYID, L M. FAJAR (Institut Pemerintahan Dalam Negeri, 2024)
Central Lombok has a high ratio and vulnerability to disasters caused by natural events. Various disaster threats caused by natural events can befall Central Lombok, such as: Floods, Extreme Waves, Earthquakes, Droughts, Extreme Weather, Landslides, Flash Floods, Tsunamis, Mount Rinjani Eruptions, and Forest & Land Fires. This research is aimed at finding out the role of the Disaster Preparedness Team in dealing with the threat of natural disasters in Central Lombok. The approach used in this research is descriptive qualitative, and data collection techniques by means of observation, interviews and literature study. This research resulted in the conclusion that the role of the Disaster Preparedness Team is still lacking due to the small number of Disaster Preparedness Teams, the lack of equipment and infrastructure to support disaster preparedness teams, and the lack of knowledge of residents about disasters. Keywords: Role, Disaster Preparedness Team, Natural Events